A Comprehensive Review of the Pharmacological Properties and Bioactive Components of Retama monosperma - El Yadini, Adil; Elouafy, Youssef; Amiri-Ardekani, Ehsan; Shafiee, Mina; Firouzi, Amirhosein; Sasani, Najmeh; Khalid, Assad; Abdalla, Ashraf N; Bakrim, Saad; Tan, Ching Siang; Goh, Khang Wen; Long, Chiau Ming *; et al. (MDPI, 2023)
Retama monosperma L. (Boiss.) or Genista monosperma L. (Lam.), known locally as "R'tam", is a spontaneous and annual herb that belongs to the Fabaceae family. It is native to the Mediterranean regions, specifically in the desert areas and across the Middle Atlas in Morocco. This plant has been extensively used in folk medicine and it is rich in bioactive compounds, including polyphenols, flavonoids, and alkaloids. Current research efforts are focusing on the development of novel natural drugs as alternatives to various organic and non-organic chemical products from Retama monosperma. In addition, extract, and isolated compounds obtained from different parts of the chosen plant have been described to exhibit multiple biological and pharmacological properties such as antioxidant, anti-aging, anti-inflammatory, antihypertensive, anti-helminthic, disinfectant, diuretic, and hypoglycemic effects. The plant-derived extract also acts as an antimicrobial agent, which is highly efficient in the treatment of bacterial, viral, and fungal infections. Its antiproliferative effects are associated with some mechanisms, such as the inhibition of cell cycle arrest and apoptosis. In light of these assessments, we critically highlight the beneficial effects of the flowers, stems, seeds extracts, and isolated compounds from R. monosperma (L.) Boiss in human health care, industrial, and other applications, as well as the possible ways to be employed as a potential natural source for future drug discovery.